Implementation of the Problem-Based Learning Model to Improve Students' Mathematics Learning Outcomes in Grade IV at SD Negeri 060916 Medan Sunggal - Frida Marta Argareta Simorangkir; Indah Simbolon; Hesty Vania Sinaga; Liza Natalia Sitopu; Ade P. Lumban Gaol; Karolina Linvia Fau (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Low mathematics achievement among fourth-grade students at SD Negeri 060916 Medan Sunggal was associated with teacher-centered instruction that restricted students’ active participation in conceptual understanding and mathematical problem-solving. This study aimed to improve students’ mathematics learning outcomes on plane geometry through the implementation of the Problem-Based Learning (PBL) model. Classroom action research based on the Kemmis and McTaggart model was conducted in two cycles, each comprising planning, action, observation, and reflection, with 24 fourth-grade students as participants. Data were collected through classroom observations, interviews, achievement tests, and documentation and analyzed using qualitative and quantitative descriptive techniques. The findings demonstrated a progressive improvement in students’ mathematics achievement, with the mean score increasing from 76.25 in the pre-cycle to 80.92 in Cycle I and 85.83 in Cycle II. Learning mastery also increased from 66.67% in the pre-cycle to 83.33% in Cycle I and 95.83% in Cycle II. In addition, the implementation of PBL enhanced students’ classroom participation, collaboration, critical thinking, and problem-solving skills. The study concludes that PBL is effective in improving mathematics learning outcomes and the quality of instruction on plane geometry. These findings provide practical evidence for elementary school teachers seeking to implement student-centered, problem-oriented learning that strengthens both academic achievement and higher-order thinking skills.